Dual inhibition of the mTORC1 and mTORC2 signaling pathways is a promising therapeutic target for adult T‐cell leukemia - Kawata, Takahito; Tada, Kohei; Kobayashi, Masayuki; Sakamoto, Takashi; Takiuchi, Yoko; Iwai, Fumie; Sakurada, Maki; Hishizawa, Masakatsu; Shirakawa, Kotaro; Shindo, Keisuke; Sato, Hironori; Takaori‐Kondo, Akifumi (Cancer science, 2018)
Adult T‐cell leukemia (ATL) has a poor prognosis as a result of severe immunosuppression and rapid tumor progression with resistance to conventional chemotherapy. Recent integrated‐genome analysis has revealed mutations in many genes involved in the T‐cell signaling pathway, suggesting that the aberration of this pathway is an important factor in ATL pathogenesis and ATL‐cell proliferation. We screened a siRNA library to examine signaling‐pathway functionality and found that the PI3K/Akt/mTOR pathway is critical to ATL‐cell proliferation. We therefore investigated the effect of mammalian target of rapamycin (mTOR) inhibitors, including the dual inhibitors PP242 and AZD8055 and the mTORC1 inhibitors rapamycin and everolimus, on human T‐cell leukemia virus type 1 (HTLV‐1)‐infected‐cell and ATL‐cell lines. Both dual inhibitors inhibited the proliferation of all tested cell lines by inducing G1‐phase cell‐cycle arrest and subsequent cell apoptosis, whereas the effects of the 2 mTORC1 inhibitors were limited, as they did not induce cell apoptosis. In the ATL‐cell lines and in the primary ATL samples, both dual inhibitors inhibited phosphorylation of AKT at serine‐473, a target of mTORC2, as well as that of S6K, whereas the mTORC1 inhibitors only inhibited mTORC1. Furthermore, AZD8055 more significantly inhibited the in vivo growth of the ATL‐cell xenografts than did everolimus. These results indicate that the PI3K/mTOR pathway is critical to ATL‐cell proliferation and might thus be a new therapeutic target in ATL. The PI3K/Akt/mTOR pathway is crucial for ATL cell survival and proliferation. The effect of mTORC inhibitors depend on the inhibition of the phosphorylation of Akt at Ser‐473. Dual mTORC1 and mTORC2 inhibitors show a potent cytotoxic effect on ATL cells and are promising agents for the treatment of ATL.